The identity of Bombyx jesuita Fabricius, 1775 (Lepidoptera: Notodontidae, Dioptinae, Josiini) - Vitor O. Becker (SHILAP, 2024)
The identity of Bombyx jesuita Fabricius, 1775, is established and assigned to Josia Hübner, [1819] as J. jesuita (Fabricius, 1775), comb. nov., senior synonym of Bombyx fulvia Cramer, 1779, syn. nov., J. ligula Hübner, [1808], syn. nov. and J. tenuivitta Butler, 1878, syn. nov. Lyces fulvia (Hübner, [1822]), stat. rev. (= Josia aurimutua Walker, 1854, syn. nov.), is reinstated.